Uncommon Ground: Ground-Encoding In Dâw Motion Verbs. - Obert, Karolin (International Journal of American Linguistics, 2026)
Cross-linguistic research shows that languages differ in how they encode the basic semantic components of motion events (figure, motion, manner, path, and ground) in their grammars and lexicons. While manner and path encoding have received significant attention, one core component has been underestimated: ground, the object or surface relative to which motion occurs. In fact, the possibility of ground being a structuring part of motion verb inventories has been previously excluded. However, novel methods of data collection and insights from underrepresented languages suggest that ground lexicalization in motion verbs is more common than assumed and can even influence basic-level motion verbs. This study examines the largely unknown semantic and morphosyntactic design space of ground-encoding motion verbs in Dâw (ISO 639-3: kwa, Naduhup, Brazil). The findings illustrate that the ground component can be deeply integrated into basic motion verb semantics and how linguistic structure, culture, and environment can impact lexical elaboration.